Comparative Assessment of Robusta Coffee Marketing Channels in Solok City, West Sumatra - Azzahra, Nadia; Mutiara, Vonny Indah; Hariance, Rika (Politeknik Pertanian Negeri Payakumbuh, 2024)
Coffee stands as a cornerstone of agricultural economies and it has significant roles in the global beverage industry in Indonesia. However, robusta coffee marketing channels issue impacts the prices received by farmers. The price that consumers pay and the price that farmers receive differ significantly. This research offers a comparative analysis robusta coffee marketing channels in Solok City of West Sumatra. This study used a purposive sampling by a survey approach. The survey method involves interviewing and giving questionnaires to 35 farmers, 5 collectors in the village, and 3 wholesalers. The findings indicated the existence of three marketing channels. The first marketing channel shows that farmers received a price of 25,722.22 IDR/kg, with a farmer share of 86.70% and an efficiency of 4.30%. The second marketing channel shows that farmers received a price of 27,812.50 IDR/kg with a marketing efficiency of 3.92% and a farmer share of 94.82%. The third marketing channel shows that farmers received a price of 25,722.22 IDR/kg and a farmer share of 100%, while the marketing efficiency of 1.77%. These findings demonstrate that marketing channel three is the most efficient. To enhance productivity, it is suggested that farmers should consider rejuvenating coffee plants and prioritize the post-harvest process to ensure hygiene and produce high-quality coffee. By increasing coffee productivity and improving coffee quality, it is expected that farmers could gain higher prices and achieve greater profitability.